Diagnosis & management of alpha-gal syndrome: lessons from 2, 500 patients. (2nd July 2020) - Commins, Scott P.
ABSTRACT: Introduction: Alpha-gal Syndrome (AGS) is a unique allergy to non-primate mammalian meat (and derived-products) that is associated with tick bites and is due to a specific IgE antibody to the oligosaccharide galactose-α-1, 3-galactose (alpha-gal). AGS has many novel features that broaden the paradigm of food allergy, including that reactions are delayed 3–6 hours after exposure and patients have frequently tolerated red meat for many years prior to the development of allergic reactions. Due to the ubiquitous inclusion of mammal-derived materials in foods, medications, personal products and stabilizing compounds, full avoidance is difficult to achieve. Areas covered: This review describes the author's experience with diagnosis, management, and design of appropriate avoidance for patients with AGS and provides clinicians with practical advice for care of these patients. Expert opinion: The number of patients with AGS is rising and may have exceeded awareness of the diagnosis amongst healthcare providers. In summarizing experience gained to thus far, we hope to create a resource for identifying and managing this unique allergic syndrome.